Shifting perspectives: challenges and changes in policy perspectives on sustainability in the agricultural sector in Flevoland, the Netherlands - Kimberly Kuipers; Edwin B. P. De Jong; Riyan J. G. Van den Born (International Journal of Agricultural Sustainability)
Policy perspectives on sustainability, particularly those dominating an era, can have long-lasting effects and shape the context in which decisions are made. Historical analyses of sustainability perspectives applied in policymaking can enrich our understanding of the sources contributing to decision-making processes. Through an in-depth analysis of policy documents published between 1986 and 2022 and interviews with former and current policymakers, we have studied the development of the Dutch regional government of Flevoland’s perspectives on sustainability in the agricultural sector. We developed a framework to guide our analysis of the concepts and rhetoric used and the assumptions made about social-ecological relationships, nature values, and structure and agency. Our findings show a gradual evolution of policy perspectives on sustainability, moving from an economic focus to recognising ecological value and the agricultural sector’s role in addressing environmental and social issues. However, aspects of social sustainability remain narrowly addressed, focusing on business aspects while overlooking farmers’ multifaceted roles and challenges. Moreover, despite encouraging farmer-led sustainability initiatives, the Province struggles to clarify its sustainability strategy and implement concrete measures. These insights can help challenge previously unquestioned or unknown assumptions and be instrumental in crafting better integrated and effective policy measures aimed at addressing sustainability challenges.